Pien-Tze-Huang alleviates CCl4-induced liver fibrosis through the inhibition of HSC autophagy and the TGF-β1/Smad2 pathway - Zhang, Yuqin; Hua, Liping; Lin, Chunfeng; Yuan, Mingzhou; Xu, Wei; Raj D., Anand; Venkidasamy, Baskar; Cespedes-Acuna, Carlos L.; Nile, Shivraj Hariram; Yan, Guohong; Zheng, Haiyin (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: Pien-Tze-Huang (PZH)—a traditional Chinese medicine (TCM) compound—has been employed to treat various liver inflammation and tumors for over 10 decades. Interestingly, most of the pharmacological effects had been validated and explored toward liver ailment along with pro-inflammatory conditions and cancer at the cellular and molecular level to date. Aim of the study: The present study aimed to investigate the therapeutic effect of PZH on autophagy and TGF-β1 signaling pathways in rats with liver fibrosis and hepatic stellate cell line (HSC). Materials and methods: Male SD rats with carbon tetrachloride (CCl4)-induced liver fibrosis were used as the animal model. Next, PZH treatment was given for 8 weeks. Afterward, the therapeutic effects of PZH were analyzed through a hepatic tissue structure by hematoxylin-eosin (H&E), Van Gieson (VG) staining, and transmission electron microscopy (TEM), activity of ALT and AST by enzyme-associated immunosorbent assay as well. Subsequently, mRNA and protein expression were examined by quantitative polymerase chain reaction (qPCR), Western blotting, and immunohistochemistry (IHC). Then, the cell vitality of PZH-treated HSC and the expression of key molecules prevailing to autophagy were studied in vitro. Meanwhile, SM16 (a novel small molecular inhibitor which inhibits TGFβ-induced Smad2 phosphorylation) was employed to confirm PZH’s effects on the proliferation and autophagy of HSC. Results: PZH pharmacologically exerted anti-hepatic fibrosis effects as demonstrated by protecting hepatocytes and improving hepatic function. The results revealed the reduced production of extracellular collagen by adjusting the balance of matrix metalloproteinase (MMP) 2, MMP9, and tissue inhibitor of matrix metalloproteinase 1 (TIMP1) in PZH-treated CCl4-induced liver fibrosis. Interestingly, PZH inhibited the activation of HSC by down-regulating TGF-β1 and phosphorylating Smad2. Furthermore, PZH down-regulated yeast Atg6 (Beclin-1) and microtubule-associated protein light chain 3 (LC3) toward suppressing HSC autophagy, and PZH exhibited similar effects to that of SM16. Conclusion: To conclude, PZH alleviated CCl4-induced liver fibrosis to reduce the production of extracellular collagen and inhibiting the activation of HSC. In addition, their pharmacological mechanisms related to autophagy and TGF-β1/Smad2 signaling pathways were revealed for the first time.